2003
DOI: 10.1038/sj.onc.1206539
|View full text |Cite
|
Sign up to set email alerts
|

HBX causes cyclin D1 overexpression and development of breast cancer in transgenic animals that are heterozygous for p53

Abstract: Transgenic mice, which selectively express the WAP-HBX transgene in mammary gland epithelial cells (ME-cells), were established in order to elucidate the consequences of HBX gene expression on organ differentiation, cell death program and tumor development. Transgene expression was demonstrable by RT-PCR, Northern and Western blot analysis during pregnancy, lactation and after weaning. HBX synthesis neither affect mammary gland differentiation nor apoptosis in ME-cells. Although breast cancer formation was rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…Previous studies reported that HBx disturbed multiple check-points in primary mouse liver cells, established cell lines, and HBx transgenic mice (6)(7)(8)(9)(10). Here, our study showed that HBx also induced cell cycle arrest at G2/M phase.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies reported that HBx disturbed multiple check-points in primary mouse liver cells, established cell lines, and HBx transgenic mice (6)(7)(8)(9)(10). Here, our study showed that HBx also induced cell cycle arrest at G2/M phase.…”
Section: Discussionsupporting
confidence: 60%
“…The effects of HBx on cell cycle progression are potentially more complicated. Some studies found that HBx stimulated cell cycle progression, accelerating transit through checkpoint controls at G0/G1 (7)(8)(9). Other reports showed that HBx could block G0/G1 and G1/S transit or had no effect on cell cycle profiles (6,10).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that HBx-mediated cyclin D1 up-regulation in mammary gland cells can induce tumors as well despite the differences between hepatocyte and mammary gland cells (18). In this report, we show that HBx up-regulates cyclin D1 in Chang liver cells (immortalized hepatocyte cell line) and HepG2.2.15 cells (HBV-producing cell line derived from hepatoblastoma cell line).…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have suggested a link between HBx and cyclin D1 where cyclin D1 is shown to be up-regulated by HBx (18). Overexpression of cyclin D1 is involved in tumor development and growth (19) as well as in HCC.…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…48,79 HBx increases the rate and level of activation of CDK2, where the rate is associated with cyclins E and A, and the level with cyclin B. 80 HBx also causes cyclin D1 overexpression, 81 the Rb gene is a key player in the G1/S checkpoint system, and HBxAg transactivates the Rb promoter. 48 Increased levels of phosphorylated Rb result in the release of E2F from Rb and cell-cycle progression.…”
Section: Ink4dmentioning
confidence: 99%